State Alcohol Policies, Taxes, and Availability as Predictors of Adolescent Binge Drinking Trajectories into Early Adulthood - Fairman, Brian J. (Addiction, 2019)
BACKGROUND AND AIMS: A number of alcohol policies in the United States have been presumed to reduce underage youth drinking. This study characterized underage youth binge drinking trajectories into early adulthood and tested associations with the strength of the alcohol policy environment, beer excise taxes, and number of liquor stores. DESIGN: Longitudinal cohort study. SETTING: USA. PARTICIPANTS: A national cohort of 10(th) graders in 2010 (n=2753), assessed annually from 2010–2015. MEASUREMENTS: Participants reported on their 30-day binge drinking (defined as consuming 5+ (for boys) or 4+ (for girls) drinks within 2 hours). We scored the strength of 19 state-level policies at baseline and summarized them into an overall score and two subdomain scores. We also assessed state beer excise taxes (dollars/gallon) and linked the number of liquor stores in 1-km to participant’s geocoded address. FINDINGS: We identified five binge drinking trajectories: low-risk (32.9%), escalating (26.1%), late-onset (13.8%), chronic (15.1%), and decreasing (12.0%). Lower overall alcohol policy strength was associated with increased risk of being in the escalating vs. low-risk binge drinking class (relative risk ratio, RRR = 1.4 per 1 SD in policy score; 95% CI [1.2, 1.8]). Higher beer excise taxes were associated with a reduced risk of being in the escalating class (RRR = 0.2 per 1 dollar increase; 95% CI [0.1, 0.6]). The number of liquor stores was not significantly associated with any binge drinking trajectory. CONCLUSIONS: In the US, stronger state alcohol policies and higher beer excise taxes appear to be associated with lower risk of escalating alcohol consumption trajectories among underage youth.